Kolaborasi dalam Penerapan Program Saber Mempro di Kecamatan Bandar Sei Kijang Kabupaten Pelalawan - Icha Khinanty; Adianto Adianto (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
The regional government of Pelalawan Regency, through the Population and Civil Registration Service of Pelalawan Regency, designed and implemented the Saber Mempro Innovation Program in collaboration with health actors (Puskesmas, Clinics, Hospitals and Village Midwives) in Pelalawan Regency to improve easy population administration services, processes fast, and free. Saber Mempro is a one file program with at least four products where this program aims to make it easier for pregnant women to take care of population administration. This research aims to describe and analyze how collaboration in implementing the Saber Mempro Program is carried out, as well as identifying and analyzing factors that support collaboration in implementing the Saber Mempro Program in Bandar Sei Kijang District, Pelalawan Regency. The method used in this research is qualitative with data collection techniques, namely interviews, observation and documentation which are then analyzed so that final conclusions can be drawn. The research results show that collaboration between parties involved in implementing the Saber Mempro Program runs well and optimally, this is due to several supporting factors that make the collaboration process in implementing the Saber Mempro program run well, namely budget, facilities and infrastructure, communication, and user participation. program.